Detection of Possible Tax-Evasive Transfer Pricing in Multinational Enterprises - Jaroslav Brada; Tomáš Buus (European Financial and Accounting Journal, 2009)
In this paper we analyze possible source of tax evasion in the multinational entity (hereinafter “MNE”). We show that the tax obligation of the whole MNE depends on the ownership structure of companies, which form MNE and that the structure could be described by matrix form. Therefore the basic tax optimization tasks of MNE via transfer pricing can be understood as linear programming problems. In addition we propose a way to identify possible tax evasion realized via transfer pricing in MNE.
Keywords: D21; D29; G39; 650; Transfer prices; Tax evasion; Tax authorities; Multinational entities; Mathematical taxation; Linear programming